TiO2-zeolite photocatalysts made of metakaolin and rice husk ash for removal of methylene blue dye - Naruemon Setthaya (2018)
© 2017 Elsevier B.V. In this study, synthesized zeolites were performed by solvothermal method using metakaolin and rice husk ash as starting materials. The TiO 2 -zeolites photocatalysts obtained from the solvothermal method was compared with that obtained from impregnation method. The synthesized products were characterized using X-ray Fluorescence spectrometer (XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM), the Fourier transform infrared (FTIR), ultraviolet -visible spectroscopy (UV–vis), particle size analyzer and surface area measurement. The results showed that the incorporation of TiO 2 in a form of transparent titanium solution into zeolites obtained from solvothermal method was very similar to that obtained from impregnation method confirmed by their mineralogical compositions, microstructures and specific surface areas. The adsorption and degradation efficiency of the TiO 2 -zeolites photocatalysts obtained from solvothermal method of 97.32% was slightly lower than 99.43% of impregnation method. In addition, the synthesized TiO 2 -zeolites photocatalysts showed a greater adsorption and degradation of methylene blue than pure zeolites and pure TiO 2 anatase.